Formas de produção pecuária e distribuição da febre aftosa no departamento de Santa Cruz, Bolívia, 2000-2007 - Hernan Oliver Daza Gutierrez (2008)
Municipies of Department of Santa Cruz, Bolivia, were characterized due to its predominant form of cattle livestock production. Demografical and movement indicators as well as Social Network Analysys were used for the study of bovine movements patterns. A center/perifery structure was identified; a relation of the forms of production with movement patterns, consiliate with the intensity and finality of the movement recorded data. The results suggest a methodological scheme as exploration tools of movement data as complementation of characterization and/or regionalization processes. The distribuition of foot and mouth disease in farms of Department of Santa Cruz 2000-2007, occur in areas where the meat transformation production system predomine, near industrialized áreas